Khoáng hóa metyl đỏ bằng phương pháp fenton điện hóa - Lê Hiền, Nguyễn Thị; Tươi, Trần Thị (Vietnam Journal of Chemistry, 2014)
To promote treatment efficiency, an efficient undivided electrochemical system using a Ppy (Cu1,5Mn1,5O4) composite film on graphite cathode with high production rate of hydrogen peroxide was applied to the electro-Fenton oxidation of a model azo dye, methyl red (MR). The influences of operating parameters including cathodic potential, Fe2+ concentration, and oxygen gas flow and initial methyl red concentration was investigated. At the conditions of cathode potential of -0.6 V versus SCE, Fe2+ concentration of 0.1 mM, a solution of methyl red of 1.85 mM could become transparent totally in 24 hours with a high current yield (200% for first one hour).